Evaluasi dan Rekomendasi Konten Instagram Sebagai Alat Pemasaran UMKM Kripjungan - Soni Santana; Adi Prehanto; Rangga Gelar Guntara (Jurnal Transformasi Bisnis Digital, 2025)
Kripjungan MSMEs faces challenges in effectively utilizing Instagram as a digital marketing tool, with content that is often irrelevant, unappealing, and inconsistent with the brand identity, leading to reduced engagement and limited business growth potential. This study aims to evaluate and provide recommendations to improve the quality of Kripjungan's Instagram content using the eight pillars of content marketing from Kingsnorth. The evaluation results indicate that the content frequently does not align with audience interests, lacks variety, and is insufficiently informative or engaging to enhance user engagement or be widely shared. The recommendations include aligning content with audience preferences, enhancing credibility through more comprehensive information, employing varied visuals, and maintaining consistency with the brand identity to strengthen relationships with the audience and support the growth of Kripjungan's business.